The quiensabe, Hedeoma piperita (Lamiaceae), a species with cultural importance in the indigenous community of San Francisco Pichátaro, Michoacán, Mexico: bases for its conservation management - Herrera, María Luisa; Rico, Yessica; Pascual-Cortes, Magdalena (Instituto de Ecología, A.C., 2021)
Background and Aims: Hedeoma piperita is a plant popularly known as quiensabe and with traditional uses by the Purépecha people of San Francisco Pichátaro in Michoacán, Mexico. Despite its cultural relevance, the populations of H. piperita have been drastically reduced due to overexploitation. This work evaluated the traditional knowledge on the biology, ecology, and management of H. piperita among the indigenous community of San Francisco Pichátaro. Moreover, we aimed to evaluate its phenological development and relationships between phenological phases and local environmental variables. Methods: We applied 75 semi-structured surveys among women and men in three age groups of the community. Phenological analyses were conducted for 31 plants established in the wild and by recording the height, total number of leaves, branches, flowers, fruits and sprouts every 15 days from March 2014 to March 2015. Significant correlations between phenological and environmental variables were calculated using Spearman’s correlation coefficients. Key results: Sixty percent of the interviewed people knew and have used H. piperita, and most of them were women (71%). Alimentary purposes (as breakfast tea) were recognized as the main use among children and young people, while adults used it mostly for medicinal purposes. However, among the interviewees, little was known about the biological and ecological aspects of the species. We found that the stages of flowering and fructification overlap with the most intensive extraction season. Conclusions: Urgent management strategies are needed to recover and maintain this species in the wild, and within the Purépecha cosmos-corpus-praxis complex.